Early radial band deflation after transradial access coronary catheterization reduces complications: a systematic review - Nugroho, Rico Maulana; Waluyo, Agung; Herawati, Tuti (Faculty of Medicine, Universitas Trisakti, 2024)
BACKGROUNDTransradial access (TRA) coronary catheterization is widely used for coronary artery disease (CAD) management. However, complications such as pain, hematoma, and radial artery occlusion (RAO) often occur due to prolonged use of radial compression bands. Early deflation protocols have been proposed to minimize these complications while maintaining effective hemostasis. This systematic review evaluates the impact of early radial band deflation protocols on reducing TRA-related complications. METHODSA systematic literature search was conducted in ProQuest, PubMed, ScienceDirect, Sage Journal, and Scopus databases, including studies published between 2018 and March 2024. Inclusion criteria focused on randomized controlled trials (RCTs), cohort studies, and quasi-experimental studies evaluating radial band deflation protocols in TRA coronary catheterization patients. Outcomes included pain, hematoma, and RAO. Twelve studies were critically appraised using the Joanna Briggs Institute (JBI) tools and synthesized using narrative and quantitative approaches. RESULTSThe review included eight RCTs, three cohort studies, and one quasi-experimental study involving a total of 4,477 patients. Findings revealed that early radial band deflation (1.5–2 hours) reduced pain and hematoma incidence compared to prolonged durations (>4 hours). RAO rates were significantly lower with gradual and early deflation protocols. However, shorter durations (<1.5 hours) slightly increased bleeding risk. Evidence supported the TR Band® Light Protocol as an effective and safe deflation strategy. CONCLUSIONEarly radial band deflation protocols effectively reduce TRA-related complications, enhancing patient comfort and safety. Standardized deflation protocols and further research, including innovative technologies, are recommended to optimize post-TRA care.